The creatine kinase conundrum: a reappraisal of the association of isotretinoin, creatine kinase, and rhabdomyolysis. (27th December 2019) - Marson, Justin W.; Baldwin, Hilary E.
Abstract: Background: Isotretinoin has been reported to elevate creatine kinase, which may lead to fatal rhabdomyolysis. Objective: To review the literature and propose practice guidelines for management of elevated creatine kinase during isotretinoin therapy. Findings: Patients have intrinsic and extrinsic qualities that may synergistically work with isotretinoin to elevate serum creatine kinase. Darker skin types and males on isotretinoin are more likely to have elevated creatine kinase. Isotretinoin may induce oxidative stress within muscle tissue, thereby leading to elevations in serum creatine kinase. Conclusion: Evidence supports a tenuous correlation between isotretinoin, elevated creatine kinase, and exercise. Physicians should consider obtaining baseline creatine kinase on elite athletes and counseling patients on risk factors that may elevate creatine kinase. However, the potential for elevated CK is not a contraindication for isotretinoin therapy.